NEW WOMEN IN MANJU KAPUR’S NOVEL A MARRIED WOMAN - Anita; Sharma, Ritu (International Journal of Psychosocial Rehabilitation, 2020)
Manju kapur is one of the successful names in the galaxy of Indian women novelists in English. She has enriched the Indian English fictional world with her great creations. Her works reflect the realistic problems in the life of Indian women with a sensitive appeal. She is a feminist writer, who gives voice to the women’s pathetic condition in a traditional and patriarchal society, where social-cultural and political circumstances are the obstacles in the way of a new woman. Her novel A Married Woman deals with the inner turmoil of a new woman, who feels a lot of difference in her life after marriage but at last she struggles for her basic rights of equality,identity and self-satisfaction.Kapur’s protagonists are mostly educated,so they are conscious for their individuality. The paper brings out the feminist views of the writer to create awareness among women for their identity and status in a family and society,a woman like Astha,the protagonist of the novel can be called a new woman who tackles the situations of her life without creating any violence but being dutiful towards her responsibilities in the family. A new woman gets satisfaction by her own way breaking the norms of traditional society where male domination is in power. Manju Kapur, a modern woman novelist like kamla Markanday, Arundhati Roy, Anita Desai, Shashi Despande, Shobha De and so on paved the way for modern new woman’s feelings. She is well aware of the condition of women in the traditional society, where they are only sub-servient and submissive and this continuous state of their life becomes the cause of their psycic and neurotic problem. They never utter a word against the male-domination. These women are considered to be ideal Indian wives. But in modern era, a woman disapproves the traditional social structure of society.She is against unjust norms and tradition and becomes a rebel rejecting the ideal image of woman. The new woman is conscious for her rights, identity, independence and personal fulfillment.The fictional writing of Manju Kapur suggests her concern towards radical feminism, emphasizing sexuality as a central basis of woman’s subordination. Indian gender ideologies have historically encouraged female effacement or self-sacrifice. Postmodern tendencies have been reflected in the fictional works of Indian women writers which pave the way to the new socio-cultural and political conditions. Conventional system in India is structured around gender discrimination approving male supremacy. A woman has no place in a family and in a society, her opinion or ideas are not considered valuable in spite of her good education and intellectual caliber. She feels frustration and at last thinks to achieve her own goal for her own satisfaction or fulfillment. She turns towards lesbian relationship without thinking about her married life. This is the unique aspect of a woman who is ready to take any risk to get equall status like men in society. Her views may seem strange to some people but it is the inner voice of a new woman who wants to enjoy full stretch of her life at any cost.